The relationship between corporate governance and foreign ownership of the banks in developing countries - Tunay, K. Batu; Yüksel, Serhat (Universidad Nacional Autonoma de Mexico, 2017)
The aim of this paper is to determine the effect of corporate governance on foreign ownership of the banks. Within this context, annual data of 65 developing countries for the periods between 2004 and 2013 was analyzed. In addition to this situation, 7 explanatory variables were used in this study in order to achieve this objective. As a result of the analysis, it was identified that there is a strong relationship between operations of foreign banks and governance levels of the countries. In this regard, it was determined that the factors of corruption, political stability, rule of law and flexibility in legal regulations affect foreign bank operations. Moreover, it was also analyzed that foreign bank operations are stronger in the countries that have low poverty, high political stability and efficient legal infrastructure. On the other hand, it was defined that strict legal regulation affects foreign bank operations negatively which shows that foreign banks prefer to enter into the countries that have flexible legal regulations. This study gives essential information to developing countries about the factors that affect the decisions of foreign banks in order to enter into a developing country. Therefore, by considering the results of this study, the authorities of these countries can have a chance to take necessary actions so as to attract foreign banks.

El objetivo de este trabajo es determinar el efecto del gobierno corporativo sobre la propiedad extranjera de los bancos. En este contexto, se analizaron los datos anuales de 65 países en desarrollo de los períodos comprendidos entre 2004 y 2013. Además de esta situación, se utilizaron 7 variables explicativas para alcanzar este objetivo. Como resultado del análisis, se identificó que existe una relación fuerte entre las operaciones de los bancos extranjeros y los niveles de gobierno de los países. A este respecto, se determinó que los factores de corrupción, estabilidad política, estado de derecho y flexibilidad en las regulaciones legales afectan a las operaciones de los bancos extranjeros. Además,se analizó que las operaciones de bancos extranjeros son más fuertes en los países que tienen baja pobreza, alta estabilidad política y una eficiente infraestructura jurídica. Por otra parte, se definió que una estricta regulación legal afecta negativamente a las operaciones de los bancos extranjeros, lo que muestra que los bancos extranjeros prefieren entrar en los países que tienen regulaciones legales flexibles. Este estudio proporciona información esencial a los países en desarrollo sobre los factores que afectan las decisiones de los bancos extranjeros antes de entrar en un país en desarrollo. Por consiguiente, al considerar los resultados de este estudio, las autoridades de estos países pueden tener la oportunidad de adoptar las medidas necesarias para que atraigan bancos extranjeros.
La relación entre gobierno corporativo y propiedad extranjera de los bancos en los países en desarrollo
Keywords: Banking; Corporate Governance; Foreign Banks; Banca; Gobierno Corporativo; Bancos Extranjeros